Bone health after menopause: effect of surgical menopaus on bone mineral density and osteoporosis - Lakshmanan, Kavitha; Dhanalakshmi, M. G.; Ganesan, Anand; Myneni, Sindhura (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Natural menopause or surgical menopause is associated with endocrinological changes and alteration in bone and mineral metabolism. Hence this study was conducted to assess the bone mineral density changes in women with surgical menopause. Methods: This is a prospective observational study conducted in the department of obstetrics and gynaecology at Sri Ramachandra medical college, which is a tertiary care teaching hospital. 60 women with surgical menopause were included in the study. BMD was assessed by dual energy X-ray absorptiometry at the lumbar spine and hip joint. All the data was entered in Microsoft excel spread sheet and analysed by using SPSS software. Results: Among 60 study subjects, 41 individuals had a normal BMD, 16 had osteopenia, and 3 were diagnosed with osteoporosis. Osteopenia and osteoporosis is significantly higher in patients who had undergone hysterectomy with removal of ovaries. Observations of osteopenia and osteoporosis were significantly higher with increasing number of years post hysterectomy. Conclusions: Prevalence of osteoporosis is high in patients who undergo hysterectomy. Oophorectomy is associated with postoperative bone loss. Targeted management strategies should include routine BMD assessment and hormone therapy improves management of bone health in this population. Further more studies are needed in large populations to test alternative treatments for post oophorectomy osteoporosis.